Structural plasticity of climbing fibers and the growth-associated protein GAP-43 - Grasselli, Giorgio; Strata, Piergiorgio (Frontiers in Neural Circuits, 2013)
Structural plasticity occurs physiologically or after brain damage to adapt or re-establish proper synaptic connections. This capacity depends on several intrinsic and extrinsic determinants that differ between neuron types. We reviewed the significant endogenous regenerative potential of the neurons of the inferior olive in the adult rodent brain and the structural remodeling of the terminal arbor of their axons the climbing fiber under various experimental conditions, focusing on the growth-associated protein GAP-43. Climbing fibers undergo remarkable collateral sprouting in the presence of denervated Purkinje cells that are available for new innervation. In addition, severed olivo-cerebellar axons regenerate across the white matter through a graft of embryonic Schwann cells. In contrast, climbing fibers undergo a regressive modification when their target is deleted. In vivo knockdown of GAP-43 in olivary neurons, leads to the atrophy of their climbing fibers and a reduction in the ability to sprout toward surrounding denervated Purkinje cells. These findings demonstrate that GAP-43 is essential for promoting denervation-induced sprouting and maintaining normal climbing fiber architecture.